Analysis of emerging disinfection by-products in drinking water - Charrois, Jeffrey (John Wiley & Sons, 2010)
Disinfection by-products (DBPs) were detected in drinking water over 35 years ago. Since then identification of DBP species has closely paralleled advances in analytical chemistry. Today over 600 individual DBP species, representing several chemical classes, have been identified in drinking water. Potential DBP health concerns reported by some toxicology and epidemiology studies include elevated risks of developing certain cancers or adverse reproductive outcomes. New drinking water regulations must be evidence-based, requiring next-generation DBP studies that better link advances in analytical methods with a focus on DBPs that have the biological plausibility to cause the adverse outcomes we seek to avoid. The strategic development of the nationwide DBP occurrence study in the United States has helped to refocus today's global DBP research agenda toward a new generation of emerging DBPs of health significance. Notable DBP classes now being studied include: halonitromethanes, haloamides, halogenated furanones, haloaldehydes, haloquinones, as well as N-nitrosamines and iodo-DBPs. Improvements in extraction, separation, and detection technologies have improved our ability to identify DBP species that were once difficult, if not impossible, to detect by gas chromatography methods. Liquid chromatography/mass spectrometry applications are providing new insights into the monitoring of nonvolatile, high-molecular-weight, highly polar, hydrophilic, and thermally labile target compounds in drinking water. On-line monitoring and expanded studies evaluating swimming pool exposures are the latest innovations in the ongoing interdisciplinary research related to the analysis of emerging DBPs.